(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the current state and future prospects of teaching foreign languages in schools. It analyzes modern approaches to language education, innovative teaching methods, and the role of communicative competence in the learning process. Special attention is paid to the integration of contemporary pedagogical technologies, learner-centered instruction, and the development of students’ linguistic, cultural, and cognitive skills. The study also highlights existing challenges in foreign language teaching and suggests possible ways to improve the effectiveness and quality of language education in general secondary schools.